PRINSIP KESATUAN, KERAGAMAN, DAN HARMONI DALAM KEPEMIMPINAN TRINITARIAN - Afaradi, Asep (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2024)
This study addresses the issue of how the doctrine of the Trinity can be applied as a model for Christian leadership that is relevant in modern churches and Christian organizations, particularly in addressing the challenges of individualism, rigid hierarchies, and role conflicts. The object of this research is the Trinitarian leadership principles rooted in the doctrine of the Trinity, focusing on the principles of unity, diversity, and harmony. The study aims to formulate the concept of Trinitarian leadership within Christian theology and analyze its relevance for leadership in churches and Christian organizations in the modern era. The research employs a qualitative method with a literature review approach. The study examines key theological works, such as those by Bavinck (2012), Zizioulas (2018), and Reeves (2012), as well as other academic writings. Data were analyzed using a content analysis approach, focusing on three main themes: unity in vision, appreciation for diversity, and harmony in conflict resolution. The findings reveal that the principle of unity in the Trinity is relevant for building a shared vision within communities, the principle of diversity strengthens team dynamics through appreciation of individuals' unique roles, and the principle of harmony fosters supportive relationships through open communication and constructive conflict management. In conclusion, the doctrine of the Trinity is not only theologically relevant but also offers an inclusive and collaborative leadership model.